2019
DOI: 10.1002/pmrj.12217
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Neurolysis for Management of Focal Spasticity in the Distal Upper Extremity

Abstract: Background When managing patients with focal spasticity, phenol neurolysis is often avoided largely because of its presumed poor adverse effect profile. It is suggested that dysesthesias may be more common with phenol neurolysis of the mixed sensorimotor nerves (eg, radial, median, and ulnar nerves) compared to neurolysis of pure motor nerves. However, these risks may be mitigated with precise localization of pure motor branches by ultrasound and electrical stimulation (EStim). Objective To explore practice pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In our recent retrospective studies (21), side effects were low in general, and dysesthesia was found only in 2 out 293 of procedures (0.7%). With combined ultrasound and electrical stimulation guidance, we did not find any documented report of dysesthesia after phenol neurolysis for the distal upper extremity muscles (22). Phenol neurolysis for nerve block have shown similar or better efficacy in spasticity reduction as compared to BoNT injection (23,24).…”
Section: Introductionmentioning
confidence: 77%
“…In our recent retrospective studies (21), side effects were low in general, and dysesthesia was found only in 2 out 293 of procedures (0.7%). With combined ultrasound and electrical stimulation guidance, we did not find any documented report of dysesthesia after phenol neurolysis for the distal upper extremity muscles (22). Phenol neurolysis for nerve block have shown similar or better efficacy in spasticity reduction as compared to BoNT injection (23,24).…”
Section: Introductionmentioning
confidence: 77%
“…Phenol neurolysis can effectively manage spasticity in several muscles innervated by the same nerve, which is helpful in managing the widespread severe spasticity in persons with DoC. It takes effect in minutes, and could be repeated in days if necessary, which is ideal for use in the inpatient setting 10,11 . BoNT injections can be used to treat small muscles (eg, the lumbricals) or neck muscles (eg, the sternocleidomastoid muscle), in order to facilitate movement for communication or environmental control.…”
Section: Discussionmentioning
confidence: 99%
“…It takes effect in minutes, and could be repeated in days if necessary, which is ideal for use in the inpatient setting. 10,11 BoNT injections can be used to treat small muscles (eg, the lumbricals) or neck muscles (eg, the sternocleidomastoid muscle), in order to facilitate movement for communication or environmental control. Finally, by utilizing a mechanism of delivery at the microgram level of dosing into the intrathecal space, ITB pumps can be efficacious in managing spasticity in the lower extremities with a potential or additional effect on the trunk and upper extremities.…”
Section: Spasticity Management In Docmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in central nervous system disorders, including stroke, brain injury, and cerebral palsy. There are small-scale promising studies reviewing their efficacy and safety for this indication, Karri et al (2020) reviewed a group of 185 patients who underwent phenol neurolysis for focal spasticity [14]. 84% of those treated reported a benefit, and promisingly, there were no major adverse events reported.…”
Section: Discussionmentioning
confidence: 99%